The Emancipation Circuit : Black Activism Forging a Culture of Freedom - Davis, Thulani (Book collections on Project MUSE., 2022)
"The Emancipation Circuit is a unique historical account of the long-term response to emancipation in African American communities in the South. Throughout this project, Thulani Davis draws from primary archival sources as well as the work of historians as a way of closely examining the emergence, sustenance, and spread of viable independent Black politics produced during slavery, the Civil War, Reconstruction, and the aftermath. What sets this book apart from other historical accounts of the quest for freedom in the South is Davis's reconceptualization of the Emancipation Circuit itself. While Davis shows the many ways that the Circuit connected communities across physical space and offered important forms of mobility for formerly enslaved people and free Black activists, she also shows how the Circuit was about much more than just physical space. Davis expands the focus to include how the Circuit engaged working people in the democratic practice of crafting a better world. More than a network of mobility, the Circuit was a network of organizing and political imagining intended to enact and defend freedom. Over the course of four sections organized by region, Davis tells the complex and newly significant story of emancipation in the South"--